ORGANIZATIONAL AND LEGAL FOUNDATIONS OF STATE SANITARY EPIDEMIOLOGICAL CONTROL (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The State Sanitary Epidemiological Control (SSEC) plays a crucial role in safeguarding public health by preventing and controlling the spread of infectious diseases. This article explores the organizational and legal foundations of SSEC, highlighting its significance in maintaining the well-being of a population. We discuss the methods employed in SSEC, present key results, delve into the discussion of challenges and strengths, and conclude with suggestions for further improvement.